(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
Buccal mucoadhesive tablets have gained significant attention as an advanced drug delivery system due to their capacity to enhance bioavailability, extend drug release, and improve patient compliance. These tablets adhere to the buccal mucosa, facilitating direct absorption into the bloodstream while bypassing first-pass metabolism and enzymatic breakdown. This method is especially advantageous for drugs with limited oral bioavailability or those that need controlled release. The formulation of buccal mucoadhesive tablets involves carefully choosing polymers, excipients, and bio-adhesive agents to ensure optimal mucoadhesion, drug release profiles, and mechanical characteristics. The adhesion mechanism relies mainly on non-covalent interactions, like hydrogen bonding and van der Waals forces, which help sustain prolonged contact between the drug and the mucosal surface. Clinically, these tablets have been effectively utilized for both systemic and localized delivery, including treatments for pain relief, cardiovascular issues, and hormone therapy. However, challenges such as the stability of formulations, variability among patients, and difficulties in large-scale production necessitate more research and technological innovation. Emerging developments in polymer science, nanotechnology, and bio-responsive drug delivery systems present significant opportunities to enhance the efficacy and efficiency of buccal drug delivery.